Guidelines for fire protection in chemical, petrochemical, and hydrocarbon processing facilities. (Center for Chemical Process Safety of the American Institute of Chemical Engineers, 2003)
While there are many resources available on fire protection and prevention in chemical petrochemical and petroleum plants-this is the first book that pulls them all together in one comprehensive resource. This book provides the tools to develop, implement, and integrate a fire protection program into a company or facility's Risk Management System. This definitive volume is a must-read for loss prevention managers, site managers, project managers, engineers and EHS professionals. Note: CD-ROM/DVD and other supplementary materials are not included as part of eBook file.
Keywords: Chemical plants -- Fires and fire prevention.; Chemicals -- Fires and fire prevention.; elektronické knihy; electronic books